TECHNICAL AND ECONOMIC JUSTIFICATION OF THE FEASIBILITY OF USING THE TECHNOLOGY OF LAYING COVERS FROM DRAINING ASPHALT CONCRETE - A.D. Zheltobriukh; V.Y. Savenko (World Science, 2023)
This study assesses the economic viability of utilizing porous asphalt concrete in comparison to crushed-mastic asphalt concrete, both of which share similar applications and use cases. Key differentiators affecting costs between these two asphalt concrete types are identified, including fuel consumption during production, material expenses, and overall mixture costs. Methodologies encompassing technical specifications and experimental investigations are applied, employing analytical and comparative techniques.A comprehensive technical and economic evaluation of porous and crushed-mastic asphalt concrete is conducted, factoring in identified cost variables. To determine comparative economic efficiency, industry-standard resource consumption metrics, material utilization norms, recommendations, and laboratory analyses are incorporated. Estimates are derived using aggregated data and the price calculator provided by the State Enterprise "DerzhdorNDI SE," referencing June 2023 data from Ukraine's infrastructure restoration and development services. Analysis reveals that, when assessing material, production, and installation costs exclusively, porous asphalt concrete demonstrates superior economic advantages. Furthermore, the study establishes that the implementation of porous asphalt concrete has the potential to reduce road accidents substantially. This reduction in accidents yields significant economic benefits by mitigating overall socio-economic losses stemming from traffic incidents, thus counterbalancing expenses associated with specific challenges linked to winter maintenance and the cleaning of asphalt pores.